Organisational purchasing of service design – Agency and client perspectives - Honkanen, Jasmin (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
There has been an increase in the interest in service design, as companies have become more customer-centric and their focus has shifted to customer experiences. The actual organisational purchasing of service design has been given little attention, until recent years. The purpose of this study is to explore the purchasing of service design from the perspectives of sellers (service design agencies) and buying clients (business organisations). In order to understand the phenomenon, also agencies and clients’ approaches to service design discipline, purchasing processes, challenges related to purchasing and ways of facilitating the purchasing are explored. The research follows qualitative research method and utilises abductive reasoning. A proposition framework was formed by combining services marketing, design and organisational buying behaviour literatures, and was tested against real-life business cases. Empirical data was gathered by interviewing eight service design agency representatives and five client representatives in Finland. The results of semi-structural interviews were analysed by finding repetitive themes. The proposition framework was updated according to interview findings. There were both similarities and differences in service design agencies and clients’ approaches to service design. Service design represents a strategic activity to both parties, and it helps in clients’ business development and in discovering opportunities. It is an ideology; a way of thinking and working. The driving force for purchasing service design seemed to be something else than service design itself. Projects have been bought for 1) change and innovation related development, 2) channel related development or for 3) customer experience related development. Seven purchasing challenge themes were recognised: 1) poor or differing service design understanding, 2) selling of service design, 3) varying expectations, 4) difficulty of pre-evaluation, 5) buyers and buying companies, 6) project process and nature and 7) unclear project results. These all can be considered to cause challenges in organisational service design purchasing. Challenges can be caused by either participant, the agency or the client, and take place at any point of the purchasing process. Some of the challenges could be considered as barriers to purchasing or they play a role in an unsuccessful service project – and therefore, result in an unsuccessful organisational purchase. Purchasing could be facilitated in various ways by either participant; some ways are more attitude based, others actionable improvements. Thesis’s theoretical and managerial findings can be utilised to both improve the selling and purchasing of service design services.